Evaluation of Service Quality and Resulting Customer Satisfaction of Malaysia Local Airlines Company - Othman, Hasbullah; Ibrahim, Irwan; Amer, Afizan; Jamil, Norina Ahmad; Masrom, Nor Ratna (New Innovations in Economics, Business and Management Vol. 5, 2022)
Purpose: The purpose of this paper is to evaluate airlines customer’s evaluation of quality toward services provided by Airline Companies and their effect on customer’s satisfaction. Design/Methodology/Approach: 100 respondents from convenience sample was used to test hypotheses for this study by using SPSS to calculate data. Findings: From the result was indicated that two of the hypotheses are supported while three are not supported with customer satisfaction of airlines service. Research Limitation/Implication: The research examines the relationship between service quality dimension and customer satisfaction in airline industry. This study focuses on the evaluation of all airline service user regarding service quality of Airlines Company. The main limitation of this study is that it focus to customer satisfaction on all Airlines Companies: thus the result cannot be generalize. Practical Implications: The results indicate that company should focus on different dimensions of airline service quality, which will lead to passenger’s satisfaction and encourage the development of long-term relationships with their customers.